Sexual dimorphic traits of the head morphology of Chinese edible frog Hoplobatrachus rugulosus in Musuan, Philippines - JASMIN S. RIZALDA; MARK LLOYD G. DAPAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rizalda JS, Dapar MLG. 2025. Sexual dimorphic traits of the head morphology of Chinese edible frog Hoplobatrachus rugulosus in Musuan, Philippines. Biodiversitas 26: 4396-4411. Sexual dimorphism in amphibians often reflects ecological pressures, reproductive strategies, and behavioral roles. This study investigated sex-based differences in head, snout, and tympanum shapes in Hoplobatrachus rugulosus using landmark-based geometric morphometric analysis. A total of 60 adult frogs (30 males, 30 females) were photographed, and 33 head, 7 snout, and 8 tympanum landmarks were digitized. Generalized Procrustes Analysis (GPA) and Relative Warp Analysis were used to assess shape variation. Statistical tests included MANOVA, Discriminant Function Analysis (DFA), and Procrustes distance calculations. Significant shape differences were found between sexes for all traits: head (p = 1.03 × 10?¹?, ?² = 0.584; Procrustes d² = 0.07), snout (p = 2.18 × 10??, ?² = 0.381; d² = 0.05), and tympanum (p = 0.0001, ?² = 0.368; d² = 0.04). DFA correctly classified 90% of individuals by head shape and 75% by snout and tympanum. Females exhibited broader, more symmetrical heads and snouts, which may support feeding efficiency and fecundity. Males displayed more irregular and asymmetrical snout and tympanum shapes, likely associated with acoustic signaling and mate competition. Fluctuating asymmetry in tympanum shape across both sexes may reflect developmental stress from environmental factors such as agrochemical use or habitat disturbance. Geometric morphometrics effectively revealed subtle shape variation overlooked by traditional methods. However, the approach requires high-quality images, technical expertise, and may not capture behavioral or physiological traits. Future research should incorporate functional data, including bite force and mating acoustics, to better understand the adaptive significance of cranial dimorphism in this species.